Smart embedded systems and applications - Motahhir, Saad (River Publishers, 2022)
This book covers a wide range of challenges, technologies and state-of-the-art for the design, development and realization of these smart and complex embedded systems and their applications; i.e., software and hardware development, with the use of digital technologies, and quality assurance for critical applications. This book starts with automotive safety systems which is one of the major functional domains. The book discusses the importance of software in automotive systems followed by an insight into Automotive Software Standards, ISO26262, and Autosar. The book further discusses the use of Processor in the loop test for an adaptive trajectory tracking control for quadrotor UAVs. The book also illustrates the role of embedded systems in medical engineering. Various innovative applications involving the concept of image processing and Internet of Things are also presented in this book. The SoC Power Estimation is also investigated. Finally, a Review of the Hardware/Software Partitioning Algorithms with some future works have been presented. this book is intended for academicians, researchers, and industrialists.
Keywords: Embedded computer systems.; elektronické knihy; electronic books